Research framework for the connection between environmental collaboration and firm performance - Laari, Sini (My University, 2013)
This thesis focuses on collaborative activities with regard to environmental issues both within the firm and outside the firm with the key suppliers and customers, i.e. internal and external environmental collaboration. Integrating environmental thinking into supply chain management has received increasing interest in recent years. The relational view and the natural resource-based-view together suggest that environmental capabilities can be built jointly with supply chain partners and used to gain sustained competitive advantage. Several studies have been undertaken to analyse the connection between environmental activities and firm performance but most studies have taken only economic performance into account. This study pays attention also to two other dimensions of firm performance, intra-firm supply chain performance and environmental performance, and aims at presenting the linkages between them and environmental collaboration. This thesis creates a research framework for the connections between environmental collaboration and firm performance and suggests approaches to analyse these. In order to find out the key concepts and their relationship, an extensive literature review is conducted. The research framework proposes a positive connection between internal and external environmental collaboration and all three dimensions of firm performance. In addition, environmental performance and intra-firm supply chain performance are expected to contribute positively to economic performance. Hence, firms are suggested to benefit from environmental collaboration both within the firm and outside the firm. Empirical testing of the developed research framework is out of the scope of this study. However, this thesis proposes using a mixed methods research approach, including survey research and multiple case studies. Finland State of Logistics 2012 survey commissioned by the Finnish Ministry of Transport and Communications and conducted by Turku School of Economics is used as an example of data for the quantitative phase. The applicability of these two methods is discussed at a general level and with regard to analysing the research framework developed in the thesis. Future research will aim at the development of the research framework and the methods in order to confirm the connection between environmental collaboration and firm performance.